Between a rock and a hard place: stigma and the desire to have children among people living with HIV in northern Uganda - Nattabi, Barbara; Li, Jianghong; Thompson, S.; Orach, C.; Earnest, Jaya (International AIDS Society, 2012)
Abstract Background: HIV-related stigma, among other factors, has been shown to have an impact on the desire to have children amongpeople living with HIV (PLHIV). Our objective was to explore the experiences of HIV-related stigma among PLHIV in post-conflictnorthern Uganda, a region of high HIV prevalence, high infant and child mortality and low contraception use, and to describehow stigma affected the desires of PLHIV to have children in the future.Methods: Semi-structured interviews were conducted with 26 PLHIV in Gulu district, northern Uganda. The interviews,conducted in Luo, the local language, were audio recorded, transcribed and then translated into English. Thematic data analysiswas undertaken using NVivo8 and was underpinned by the ‘‘Conceptual Model of HIV/AIDS Stigma’’.Results: HIV-related stigma continues to affect the quality of life of PLHIV in Gulu district, northern Uganda, and also influencesPLHIV’s desire to have children. PLHIV in northern Uganda continue to experience stigma in various forms, including internalstigma and verbal abuse from community members. While many PLHIV desire to have children and are strongly influenced byseveral factors including societal and cultural obligations, stigma and discrimination also affect this desire. Several dimensionsof stigma, such as types of stigma (received, internal and associated stigma), stigmatizing behaviours (abusing and desertion)and agents of stigmatization (families, communities and health systems), either directly, or indirectly, enhanced or reducedPLHIV’s desire to have more children.Conclusions: The social-cultural context within which PLHIV continue to desire to have children must be better understoodby all health professionals who hope to improve the quality of PLHIV’s lives. By delineating the stigma process, the paperproposes interventions for reducing stigmatization of PLHIV in northern Uganda in order to improve the quality of life and healthoutcomes for PLHIV and their children.